Acceptability study of different flavors of potato piyaya (piaya) - Foyo, Jonah Maica, author; Miraballes, Janna Rose M., author; Parani, Cristal May G., author; Emelo, Marian A., adviser; Patawi, Armilyn S., technical adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2019)
Thesis Abstract
An Undergraduate Thesis (BSHRM)--Cavite State University-CCAT Campus, 2019.
Includes bibliographical references and appendices.
In English text.
Keywords: Piaya; Muscovado-filled flatbread; Potato filling; Filipino cuisine; Food innovation; Innovative flavors; Acceptability study; Experimental research; Taste evaluation; Qualitative descriptive design